2017
DOI: 10.3389/fmicb.2017.01439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1,1,1-Trichloroethane and Triclocarban on Reductive Dechlorination of Trichloroethene in a TCE-Reducing Culture

Abstract: Chlorinated compounds were generally present in the environment due to widespread use in the industry. A short-term study was performed to evaluate the effects of 1,1,1- trichloroethane (TCA) and triclocarban (TCC) on trichloroethene (TCE) removal in a reactor fed with lactate as the sole electron donor. Both TCA and TCC inhibited TCE reduction, but the TCC had a more pronounced effect compared to TCA. The TCE-reducing culture, which had never been exposed to TCA before, reductively dechlorinated TCA to 1,1-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…, PCBs and PBDEs), threatening survival of the exogenous OHRB at the sites. Moreover, various organohalides may coexist at contaminated sites, which usually cause inhibitory, occasionally stimulatory effects on microbial reductive dehalogenation. Soil and sediment are the sink of hydrophobic organohalide pollutants, where both chloroethenes and PBDEs have been detected. However, the effects of co-contaminant PCE on the performance of bioaugmentation using exogenous OHRB like Dehalococcoides remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…, PCBs and PBDEs), threatening survival of the exogenous OHRB at the sites. Moreover, various organohalides may coexist at contaminated sites, which usually cause inhibitory, occasionally stimulatory effects on microbial reductive dehalogenation. Soil and sediment are the sink of hydrophobic organohalide pollutants, where both chloroethenes and PBDEs have been detected. However, the effects of co-contaminant PCE on the performance of bioaugmentation using exogenous OHRB like Dehalococcoides remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Desulfovibrio species were found. They are metabolically versatile microorganisms capable of anaerobic sulfate reduction and RD ( Men et al, 2013 ; Mao et al, 2017 ; Wen et al, 2017 ; Lim et al, 2018 ), already detected in TCE-consortia enriched on a variety of electron donors ( Kotik et al, 2013 ). Some Desulfovibrio species (i.e., D. vulgaris and D. desulfuricans ) were previously described as capable of heavy metal reduction in anaerobic environments ( Franco et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…47−51 The co-contaminants 1,1,1-trichloroethane, triclocarban, and chloroform have been shown to impact specific Dhc strains, typically having a greater impact on cells harboring vcrA than those harboring tceA. 6,52,53 One study 31 demonstrated that PFAAs can inhibit TCE degradation by Dhc strain 195 (harboring the tceA gene) but did not examine the strainspecific impact of PFAAs on a culture containing multiple Dhc strains.…”
Section: Introductionmentioning
confidence: 99%
“…Since specific Dhc strains are necessary to fully transform PCE to ethene, understanding strain-specific impacts of co-contaminants is essential to successful EISB. Geochemical parameters, including oxygen concentration, temperature, and pH, have been shown to impact RDase gene abundance and tend to most inhibit cells harboring the vcrA gene. The co-contaminants 1,1,1-trichloroethane, triclocarban, and chloroform have been shown to impact specific Dhc strains, typically having a greater impact on cells harboring vcrA than those harboring tceA . ,, One study demonstrated that PFAAs can inhibit TCE degradation by Dhc strain 195 (harboring the tceA gene) but did not examine the strain-specific impact of PFAAs on a culture containing multiple Dhc strains.…”
Section: Introductionmentioning
confidence: 99%